Principle centered leadership - Covey, Stephen R. (A Fireside, 1991)
The great "angst" of life has seemingly gripped us all, and there seems to be no limit to the number of writers offering answers to the great perplexities of life. Covey, however, is the North Star in this field. Following his successful Seven Habits of Highly Effective People (S. & S., 1989), Covey now responds to the particular challenges of business leaders by applying his natural laws, or principles, of life to organizations. Covey explains these laws (security, guidance, wisdom, and power), and discusses how seven-habits practice and focus on these principles will result in personal and organizational transformation. He reminds us that personal and organizational success is hard work, requires unwavering commitment and long-term perspective, and is achievable only if we are prepared for a complete paradigm shift in our perspective. Without hesitation, strongly recommended for all management collections.